2014
DOI: 10.1007/s11120-014-0021-9
|View full text |Cite
|
Sign up to set email alerts
|

Amphiphilic, hydrophilic, or hydrophobic synthetic bacteriochlorins in biohybrid light-harvesting architectures: consideration of molecular designs

Abstract: Biohybrid light-harvesting architectures can be constructed that employ native-like bacterial photosynthetic antenna peptides as a scaffold to which synthetic chromophores are attached to augment overall spectral coverage. Synthetic bacteriochlorins are attractive to enhance capture of solar radiation in the photon-rich near-infrared spectral region. The effect of the polarity of the bacteriochlorin substituents on the antenna self-assembly process was explored by the preparation of a bacteriochlorin-peptide c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

8
1

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…Förster energy‐transfer calculations were also performed. In our prior studies such calculations revealed that trends in Φ EET are consistent with Förster (through‐space) energy transfer and reflect differences in the relevant photophysical properties of the donor and acceptor molecules . (The alternative is Dexter (through‐bond) energy transfer; the chromophores in the antenna systems described herein are generally expected to be too far apart for a through‐bond mechanism to make a substantial contribution.)…”
Section: Resultsmentioning
confidence: 71%
“…Förster energy‐transfer calculations were also performed. In our prior studies such calculations revealed that trends in Φ EET are consistent with Förster (through‐space) energy transfer and reflect differences in the relevant photophysical properties of the donor and acceptor molecules . (The alternative is Dexter (through‐bond) energy transfer; the chromophores in the antenna systems described herein are generally expected to be too far apart for a through‐bond mechanism to make a substantial contribution.)…”
Section: Resultsmentioning
confidence: 71%
“…One area entails utilization of the PEGylated molecules as light-harvesting constituents in biohybrid antenna complexes via attachment at hydrophilic terminal regions of membrane-spanning photosynthetic peptides. 53 A second research area focuses on the utilization of the PEGylated (bacterio)chlorins as fluorophores in clinical diagnostics, particularly flow cytometry, where antibodies are to be multiply labeled. While diverse porphyrins have been used in bioconjugation studies, 24,54 few PEGylated synthetic chlorins have heretofore been reported, 5558 and only one was equipped (but not tested) with a bioconjugatable tether.…”
Section: Introductionmentioning
confidence: 99%
“…25,26,49,[59][60][61][62][63] The design, synthesis, and physicochemical characterization of the substituted bacteriochlorins described herein provide a small step toward this goal. Ultimately one goal is not only to solubilize bacteriochlorin monomers but to be able to create multipigment architectures containing bacteriochlorins that are water-soluble for use in diverse scientific applications.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 The tetrapyrroles of present interest are bacteriochlorins, which absorb strongly in the near-infrared (NIR) region. Herein, a set of bacteriochlorins bearing distinct polar motifs is reported.…”
mentioning
confidence: 99%